Pengaruh Media Video Edukasi Tentang Vulva Hygiene Terhadap Tingkat Pengetahuan dan Sikap Remaja Putri - Halimil Umami; Fuji Rahmawati; Mutia Nadra Maulida (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
Vulva hygiene is an effort to maintain the cleanliness and health of the feminine area to avoid infectious diseases of reproduction caused by viruses, bacterias, and fungis. According to WHO, 75% of women in the world have experienced vaginal discharge that can be accompanied by candidiasis or bacterial vaginosis at least once in their life, 45% of them have experienced vaginal discharge 2 or more times. In Indonesia in 2012 almost 70% of women have experienced vaginal discharge. The highest prevalence of reproductive tract infections (ISR) in Indonesian, there were teenagers’ (42%). The teenagers' knowledge in Al-Ittifaqiah Indralaya Islamic boarding school of vulva hygiene were still low, so it was feared that the negative impact of not taking care vulva hygiene could be occurred. The use of educational videos was expected to improve teenagers' knowledge and attitude well. This study aimed to determine the effect of health education by using educational videos on the level of teenagers' knowledge and attitude about vulva hygiene at Al-Ittifaqiah Indralaya Islamic boarding school. The design of this study was pre-experimental with one group pre-posttest design. The population in this study was teenangers' class VIII MTs. Al-Ittifaqiah Indralaya with a sample of 76 respondents with a purposive sampling technique. The research instrument used a questionnaire, univariate data analysis used percentages and bivariate analysis used the Marginal Homogeneity test and the McNemar test. The results of the knowledge analysis using the Marginal Homogeneity test showed that there was a significant difference in the teenagers' knowledge before and after being given health education with a p-value of 0.000 (p <0.05). The results of the analysis of attitudes using McNemar test showed that there were significant differences in the teenagers' of attitudes before and after being given health education with a p-value of 0.000 (p <0.05). So it could be concluded that there was a significant influence on the teenagers' knowledge and attitudes before and after being given health education through educational video media about vulva hygiene. Educational video learning media was expected to become a health education program through school's health clinic (UKS) of Al-Ittifaqiah Islamic boarding school in order to increase the teenagers' knowledge and attitudes, especially regarding vulva hygiene.